Marcadores de tempo Apyãwa: a solidariedade entre os povos e o ambiente que habitam - Severino Filho, João [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This text presents the results of a Doctorate research on Mathematics Education carried out from an experience in Ethnography, with the Apyãwa Indigenous people, inhabitants of the Urubu Branco Indigenous Area, located in East Araguaia, Mato Grosso, Brazil. The main goal was to compose a set of studies and reflections on Indigenous people knowledge and their epistemologies, interpreted from the flow of Apyãwa people's social speech, from the perspective of Ethnomathematics Program. The reflections were made round the theme Indigenous Time Markers, which express knowledge produced from different ways of relating to the environment that they inhabit. This work was organized guided by the understanding of culture defined by Geertz (2008), as a symbolic web woven into the relationship between the ethos and the worldview of a people who in weaving it, establishes links and attaches to it. The Apyãwa people produce, socialize and update their knowledge, which analysis gives rise to Ethnography. The immersions took place over the years 2013 and 2014, 15 days each on average, and were interspersed with periods of detachment of the field for discussions and reflections with the supervisor and research group. The ethnography practiced with the Apyãwa people represented the possibility of realizing the cultural web being woven; of participating in a historical period of knowledge being produced, updated and taught as an intrinsic part of their cultural practice, and of hearing the narratives which explain and justify this practice. Finally, it was the possibility of contemplating, in all of this complexity, the nuances of personality, the way to interact with each other and with the environment in which they live, that constitute the Apyãwa people and that distinguishes them as a cultural group

Este texto apresenta os resultados da pesquisa de doutorado em Educação Matemática, realizada a partir de uma experiência em etnografia, junto ao povo indígena Apyãwa, habitantes da Área Indígena Urubu Branco, situada na Região do Médio Araguaia, Mato Grosso, Brasil, com o objetivo central de constituir um conjunto de estudos e reflexões sobre os conhecimentos de povos indígenas e suas epistemologias, interpretados a partir do fluxo do discurso social Apyãwa, na perspectiva do Programa Etnomatemática. As reflexões se deram em torno do tema Marcadores de Tempo Indígenas que expressam conhecimentos produzidos a partir diferentes modos de se relacionar com o ambiente que habitam. A organização do trabalho orientou-se no entendimento de cultura definido por Geertz (2008), como uma teia simbólica, tecida na relação entre o ethos e a visão de mundo de um povo - que ao tecê-la estabelece vínculos, a ela se prende. Produz, socializa e atualiza seus conhecimentos - que cuja análise suscita a etnografia. As imersões ocorreram durante os anos de 2013 e 2014, com duração média de 15 dias, eram intercaladas por períodos de distanciamento do campo para discussão e reflexão junto ao orientador e grupo de pesquisa. Praticar etnografia junto ao povo Apyãwa representou a possibilidade de perceber a teia cultural sendo tecida; de participar de um período histórico do conhecimento sendo produzido, atualizado e ensinado como parte intrínseca a sua prática cultural e de ouvir narrativas que explicam e justificam essa prática. Enfim, foi a possibilidade de contemplar, em toda essa complexidade, as nuances da personalidade, do jeito de interagir com o outro e com o meio em que se vive, que constituem o povo Apyãwa e que o distingue enquanto grupo cultural
Keywords: Mathematics - Study and teaching; Matemática - Estudo e ensino; Etnomatematica; Etnologia; Nativos; Tempo; Cultura; Mato Grosso